FILARIASIS –CASE STUDY - PROF.MRS. KR.VASANTHAKOHILA, (International Journal of Pharma and Bio Sciences, 2016)
Filariasis is a global problem. It is a major social and economic scourage in the tropics and subtropics .Lymphatic Filariasis is a parasitic disease covers infection with closely related nematode worms- W.bancrofti, B.malayi and B .timori. All three parasites have basically similar life cycles in man- adult worms living in lymphatic vessels whilst their offspring, the microfilariae circulate in the peripheral blood and are available to infect mosquito vectors when they come to feed. Filariasis is transmitted by the bite of infected vector mosquitoes. The parasite is deposited near the site of puncture. It passes through the punctured skin or may penetrate the skin on its own and finally reaches the lymphatic system. The dynamics of transmission depends upon the man- adult contact. Climate is a important factor in the epidemiology of filariasis. It influences the breeding of mosquitoes, their longevity and also determines the development of parasite in the insect vector. Lymphatic filariasis is also associated with bad drainage. Inadequate sewage disposal and lack of town planning have aggravated the problem of filariasis in India. The time interval between inoculation of infective larvae and the first appearance of detectable Mf is known as “pre patent period”. The time interval from invasion of infective larvae to the development of clinical manifestation is known as the “Clinical incubation period”. This period most commonly is 8 to 16 months. Clinical symptoms are Recurrent fever with chills, Pain in various organs, Swelling with redness in lymph’s, Urticaria, Erythematous rashes, Conjunctivitis , Pleurisy, Enlarged tender lymph nodes, Palpable lymphatic vessels. Treatments are Suramin –effective against adult roundworms Diethylcarbamazine (DEC) – treatment for W. bancrofti, Albendazole and Flubendazole – eliminate roundworms easily.